Bentuk Adaptasi Suku Bajo pada Kegiatan Usahatani (Studi Kasus pada Masyarakat Suku Bajo di Desa Jawi-Jawi Kecamatan Bungku Selatan Kabupaten Morowali - Dahlan, Dahlan; Batoa, Hartina; Mardin, Mardin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This study aims to determine the adaptation form of the Bajo tribe in case study farming activities in the Bajo community in Jawi-Jawi Village, Bungku Selatan District, Morowali Regency. The research was conducted in March 2019 in Jawi-Jawi Village, Bungku Selatan District, Morowali Regency. The informants in the study were people who knew the problems to be studied, namely 8 people consisting of fishermen from the Bajo tribe who did farming, village heads, village secretaries, and community leaders. The technique of determining research informants using the purposive sampling technique. The analysis used is descriptive qualitative analysis. The results showed that the form of adaptation of the Bajo tribe to farming activities was conducting land processing, selecting seeds, planting, fertilizing, controlling weeds, and harvesting in cultivating cassava, corn, and vegetables as one of the basic needs of the family in the southern season.